2016
DOI: 10.1002/pra2.2016.14505301097
|View full text |Cite
|
Sign up to set email alerts
|

Do medical professionals tag images differently from non‐medical professionals? An implication of retrieving user‐generated images of everyday medical situations

Abstract: Mobile photography not only allows people to take and share photos of everyday life, but also demonstrates the capability of emergency and crisis reporting at a critical moment. These images of everyday medical situations help the public understand the first-hand situation of those dramatic events, and facilitate the medical professionals to allocate medical resources and effectively diagnose. However, as the world is becoming more globalized and the communication between physician and patients is becoming mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…At the same time, students did not integrate expert tags when those were provided to them. Similarly, another study found that medical experts used fewer and more direct tags than laypeople when cataloging the same images (Phoebe, Wei-Chung, Kai-Ying, Chia-Chi, & Shing, 2016). These studies suggest that experts are more economical than novices in their tagging practices, and that they draw upon a shared knowledge base.…”
Section: Accuracy Of Novice Taggingmentioning
confidence: 94%
“…At the same time, students did not integrate expert tags when those were provided to them. Similarly, another study found that medical experts used fewer and more direct tags than laypeople when cataloging the same images (Phoebe, Wei-Chung, Kai-Ying, Chia-Chi, & Shing, 2016). These studies suggest that experts are more economical than novices in their tagging practices, and that they draw upon a shared knowledge base.…”
Section: Accuracy Of Novice Taggingmentioning
confidence: 94%
“…Resonance Imaging (MRI), and Ultrasound, 15 which play an important role in the diagnosis and treatment of diseases. Consideration has been…”
Section: Context Of Our Studymentioning
confidence: 99%
“…Tagging approach, a representation of semantic interpretations, has proven benefits on managing, searching, and discovering pictures for specific use. 15 The graph-based tag recommendation approach aims to describe and organize the patients' medical images. The recommendation of tags will suggest related diseases improving the description of the patients' medical images.…”
Section: Context Of Our Studymentioning
confidence: 99%
See 2 more Smart Citations